The Amount of Plasminogen, Tissue-Type Plasminogen Activator and Plasminogen Activator Inhibitor Type 1 in Human Thrombi and the Relation to IVVO-TNO Lysibility - Loon, B J Potter van; Rijken, D C; Brommer, E J P; van der Maas, A P C (Thrombosis and Haemostasis, 1992)
Thrombolytic therapy successfully reopens obstructed blood vessels in the majority of cases. However, it is not known why a substantial amount of thrombi are resistant to lysis by a fibrinolytic agent. In vitro studies have demonstrated that tissue-type plasminogen activator (t-PA) and plasminogen incorporated in the clot (during formation) increase lysibility. To test whether lysibility of in vivo formed human thrombi is related to their composition, we studied 25 venous thrombi obtained at autopsy and 21 arterial thrombi obtained during embolectomy.Plasminogen activator inhibitor-1 (PAI-1) antigen was measured in a phosphate-buffered saline (PBS) extract of each thrombus; t-PA antigen and plasminogen antigen were determined in a 6 M urea extract of the thrombus, representing bound proteins. Lysibility was measured as weight reduction during 8 h of incubation in PBS containing streptokinase (SK) 100 U/ml, corrected for spontaneous lysis, reflected by weight loss in PBS without SK. In addition, lysibility in SK was compared with lysibility in urokinase (UK) 100 U/ml and in t-PA 200 U/ml.Spontaneous lysis amounted to 29 ± 5% (mean ± SEM) and 33 ± 5% in venous and arterial thrombi, respectively, and inversely correlated with the PAI-1 content of thrombi (r = —0.43, p <0.01). Lysibility amounted to 76 ± 6% in venous and 90 ± 4% in arterial thrombi (venous vs. arterial: p = 0.051). PAI-1-, plasminogen- and t-PA-content of venous thrombi were 902 ± 129 ng, 34.3 ± 4.8 pg and 26.7 ± 3.0 ng per gram of wet thrombus respectively; for arterial thrombi these values were 2,031 ± 401 ng/g (p = 0.011), 64.1 ± 11.4 pg/g (p = 0.088) and 62.2 ± 8.3 ng/g (p = 0.0001), respectively. A correlation was found between t-PA and plasminogen (r = 0.74, p <0.001). Lysibility by SK related to plasminogen content in both venous (r = 0.60, p <0.002) and arterial (r = 0.44, p <0.05) thrombi; PAI-1 and t-PA did not correlate with lysibility. Lysibility in the chosen concentrations of SK, UK and t-PA were similar.We conclude that spontaneous lysis of thrombi in saline is dependent on PAI-1 content and that susceptibility of thrombibi to lysis by SK ex vivo is dependent on the plasminogen content